Strategic Management in Digital Women Entrepreneurship : A Systematic Literature Review - Dale, Priyanka; Saha, Gour C. (AMC Indian Journal of Entrepreneurship, 2023)
Purpose : As Internet usage rises in underdeveloped nations, women have embraced digital tools to start businesses. This study examined digital women entrepreneurs’ strategic choices, components, and trade-offs to obtain a competitive edge in the digital market while considering certain cultural and socioeconomic elements. Methodology : A total of 77 publications were chosen for bibliometric analysis, bibliographic coupling, literature review, network analysis, and content analysis using the Scopus database. Findings : Despite growing interest in digital entrepreneurship, gender-based research remains scattered. Women entrepreneurs adopted strategic choices such as entrepreneurial leadership, risk-taking, diversification, skill augmentation, personalized service, and appropriate pricing to compete with larger internet giants. When making strategic decisions, women draw on their networks and peer networks. In underdeveloped nations, female entrepreneurs needed specific support systems, strategies, tactics, and performance metrics to succeed in digital businesses. Practical Implications : The comprehension of strategic management methods among female digital entrepreneurs was improved by this paper. The results showed that methods encouraging womenâ€™s digital inclusion in pursuing entrepreneurial goals should be developed. Originality : To our knowledge, this review was the first to use bibliographic coupling as the analytical approach and concentrate on the strategic management of women-run digital firms.